2020
DOI: 10.1111/jocd.13453
|View full text |Cite
|
Sign up to set email alerts
|

Variation of biophysical parameters of the skin with age, gender, and lifestyles

Abstract: Background: Sweet, spicy or greasy food, staying up late, and using electronic products for a long time are common bad habits nowadays. Their role in skin diseases has been paid much attention. Objective: The aim of this study was to investigate whether unhealthy lifestyles would affect the skin sebum content, SC hydration, and pH and how do they affect. Methods: A total of 300 volunteers were enrolled, and a multifunctional skin physiology monitor measured the three skin biophysical properties on the forehead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
(71 reference statements)
1
6
0
Order By: Relevance
“…As the cutaneous sebum content is influenced by androgens on the male and estrogens on the female side, 49 these results are comprehensible. Our findings are in accordance with earlier studies investigating the sebum content at the forehead of Asian 50 and Caucasian 51 men and women. In conformity with results obtained by Luebberding et al., 51 the Skinly measurements showed that sebum levels in men remained relatively stable after the age of 40, while in women, sebum levels began to decline at the same age.…”
Section: Discussionsupporting
confidence: 94%
“…As the cutaneous sebum content is influenced by androgens on the male and estrogens on the female side, 49 these results are comprehensible. Our findings are in accordance with earlier studies investigating the sebum content at the forehead of Asian 50 and Caucasian 51 men and women. In conformity with results obtained by Luebberding et al., 51 the Skinly measurements showed that sebum levels in men remained relatively stable after the age of 40, while in women, sebum levels began to decline at the same age.…”
Section: Discussionsupporting
confidence: 94%
“…In the case of TEWL, the changes in TEWL were measured to evaluate the disruption of the skin water barrier function. 61,69 As shown in Fig. 10D, the TEWL values did not differ significantly before (6.42 ± 1.85 g mL −2 h −1 ) and after the application of the DMN (6.78 ± 2.10 g mL −2 h −1 ).…”
Section: Resultsmentioning
confidence: 75%
“…band reflectance spectrophotometry at a wavelength of 550 nm and 660 nm for erythema and melanin, respectively. 53,61 In the case of skin melanin, the amount of skin pigmentation recorded after a 24 h application of the DMN patches (93.89% melanin index relative to the normal skin measurements) was slightly decreased compared with that before the application (100% melanin index) (Fig. 10A).…”
Section: Biomaterials Science Papermentioning
confidence: 96%
“…The sleep patterns of the volunteers were obtained through the Self-Evaluation Questionnaire using questions including “At what time do you usually fall asleep on weekdays or workdays (hour, AM or PM)?”, “At what time do you usually fall asleep on weekends or your non-work days (hour, AM or PM)?”, “How much time do you usually sleep on weekdays and weekends (hour)?” and “Do you have sleep problems?”. According to several sleep-related studies, 7 , 24 it is generally believed that falling asleep after 11:00 PM belongs to late sleep time, so in our study bedtime was classified as 11:00 PM, then the volunteers were divided into early bedtime group (S0) and late bedtime group (S1). The basic information of the subjects in each group is summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%